Adherence to Urological Therapies for Lower Urinary Tract Symptoms Due to Benign Prostatic Enlargement During COVID-19 Lockdown - Morgia, Giuseppe; Lo Giudice, Arturo; Asmundo, Maria Giovanna; Rapallo, Ilenia; Carrino, Maurizio; Persico, Francesco; Terrone, Carlo; Malinaric, Rafaela; Tedde, Alessandro; Madonia, Massimo; Voce, Salvatore; Reale, Giulio; et al. (Frontiers in Urology, 2022)
Background Due to the pandemic emergency caused by COVID-19, many countries were forced to apply a variety of measures such as quarantine and full national lockdown in order to contain the contagion. Medication adherence to chronic diseases may have been negatively influenced by restrictions due to the COVID-19 pandemic. The purpose of this study is to investigate adherence to urological therapies of patients with lower urinary tract symptoms (LUTSs) secondary to benign prostatic hyperplasia (BPH) during the COVID-19 lockdown period. Methods In this cohort study, we included a total of 151 male patients who were prescribed medications for LUTSs/benign prostatic enlargement (BPE) between January 2019 and December 2020. The prescriptive data of the following medications were collected: alpha-blockers (AB), 5-alpha reductase inhibitors (5-ARIs), 5-phosphodiesterase inhibitors (PDE5-i), antimuscarinics, and phytotherapy (i.e., Serenoa repens). According to adherence or discontinuation of therapy, patients were divided into two groups: those who took their medications for a minimum of 6 months during the index period were considered in the “Medication adherence group” and those whose treatment was considered “discontinued” if it was interrupted for a 1-month period. Results Overall, the median age was 69.0 (interquartile range [IQR]: 63.0–74.0), the median International Prostate Symptom Score (IPSS) before the lockdown was 15.0 (IQR: 11.0–18.0), and the median IPSS–quality of life (IPSS-QoL) before the lockdown was 2.0 (IQR: 2.0–3.0). During the lockdown, 19 patients (12.58%) stopped taking their medications due to the pandemic situation: six (31.58%) stopped phytotherapy, two stopped AB+phytotherapy (10.53%), five stopped AB (26.32%), three stopped 5-ARIs (15.79%), one stopped antimuscarinics (5.26%), and two stopped other combination therapies (p < 0.01). Among the patients who stopped therapy, five (26.31%) reported the presence of worsening symptoms (score ≥ 3), while 14 (73.69%) reported the absence of worsening symptoms (score < 3). During the lockdown, five (3.31%) patients required hospitalization: three (1.99%) for acute urinary retention and two (1.32%) for urinary tract infection. Conclusions The rate of medication adherence for LUTSs/BPE during COVID-19 was 86.75%, but 13.25% of the patients had their treatments interrupted due to the pandemic situation. This rate determined a slight increase in symptoms with a potential impact on hospitalization. These results should be taken into account in order to develop adequate strategies in telehealth to maintain medication adherence for chronic diseases.